2006
DOI: 10.1371/journal.pbio.0040072
|View full text |Cite|
|
Sign up to set email alerts
|

A Map of Recent Positive Selection in the Human Genome

Abstract: The identification of signals of very recent positive selection provides information about the adaptation of modern humans to local conditions. We report here on a genome-wide scan for signals of very recent positive selection in favor of variants that have not yet reached fixation. We describe a new analytical method for scanning single nucleotide polymorphism (SNP) data for signals of recent selection, and apply this to data from the International HapMap Project. In all three continental groups we find wides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

102
3,588
8
17

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,545 publications
(3,782 citation statements)
references
References 55 publications
102
3,588
8
17
Order By: Relevance
“…We checked the Haplotter website 14 for evidence of recent positive selection in the region based on analysis of Hapmap data, but no genes in the maximally linked region were assigned a significant P-value for evidence of positive selection, although there were some extreme scores of Fay and Wu's H and Tajima's D, which are both based on detecting shifts in the frequency spectrum of polymorphisms. 14 However, these measures are best calculated from resequencing data, rather than Hapmap data, which are based on a preselection of SNPs and do not give an unbiased assessment of the true frequency spectrum of polymorphisms, so at the moment the evidence for selection at this locus remains equivocal.…”
Section: Resultsmentioning
confidence: 99%
“…We checked the Haplotter website 14 for evidence of recent positive selection in the region based on analysis of Hapmap data, but no genes in the maximally linked region were assigned a significant P-value for evidence of positive selection, although there were some extreme scores of Fay and Wu's H and Tajima's D, which are both based on detecting shifts in the frequency spectrum of polymorphisms. 14 However, these measures are best calculated from resequencing data, rather than Hapmap data, which are based on a preselection of SNPs and do not give an unbiased assessment of the true frequency spectrum of polymorphisms, so at the moment the evidence for selection at this locus remains equivocal.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout we have assumed that positive selection occurs only through completed hard selective sweeps. Indeed soft sweeps (Innan and Kim 2004;Hermisson and Pennings 2005;Pennings and Hermisson 2006;Garud et al 2015) and partial sweeps Sabeti et al 2002;Voight et al 2006), may be widespread, and differ in their effects on linked polymorphism (Orr and Betancourt 2001;Meiklejohn et al 2004;Przeworski et al 2005;Teshima et al 2006;Schrider et al 2015;Vy and Kim 2015). Polygenic selection, in which alleles at several different loci underlying a trait under selection will experience a change in frequency, is also thought to be widespread (Pritchard et al 2010;Berg and Coop 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These include metrics for measuring population differentiation (for example, F statistic (F st )) or unusual patterns of haplotypes (for example, integrated haplotype score, and cross-population extended haplotype homozygosity (XP-EHH)) that are suggestive of recent selection driven population sweeps. [1][2][3][4][5] Most of these studies have focused on differences between different continental groups. Although the number of studies examining differences within European populations has thus far been more limited, similar studies have identified the lactase gene as well as several genes that determine eye color.…”
Section: Introductionmentioning
confidence: 99%